PENAL SYSTEMS OF CRIMINAL CODES OF SOME COUNTRIES OF THE EUROPEAN UNION: COMPARATIVE LEGAL ANALYSIS - Рибікова, Ганна Володимирівна; Проскура, Тетяна Борисівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Goal: the development of proposals to improve the system of punishments in Ukraine and certain types of punishments provided by the Criminal Code of Ukraine based on the analysis of the system of punishments using Criminal Codes of some European countries. Methods of research: in the given paper there were used such methods as dialectical method of cognition, general scientific and special methods. Results: it was suggested to simplify the system of punishments in Ukraine following the examples of France, Italy and Kingdom of Netherlands, to change the wording of the legal criminal law due to the requirements of the international law. Discussion: the search for the ways of improving the system of punishments of the Criminal Code of Ukraine on the basis of the experience of the European countries. The Criminal Code of Ukraine contains an exclusive list of penalties for criminal offenses, the purpose of which is not only to punish the perpetrators, but also their correction and preventive influence on the society. However, for the guaranteed achievement of these goals, as foreseen by the criminal law, further improvement of the existing system of punishment is necessary. At the same time, guided by the European standards of society, when improving certain types of punishment, it is necessary to proceed from the existing successful European experience. At present, there is a lack of meaningful research on comparative and systemic punishment systems in countries such as France, the Kingdom of the Netherlands and Italy to improve Ukrainian legislation in terms of reforming, changing and improving both the penal system as a whole and certain types of punishment for criminal offenses. That is why the authors revealed the distinctive features of the penal system of the three European countries, whose criminal law developed beyond the influence of the socialist system of law of the USSR. Also, for a full disclosure of the subject of penal systems it is not enough to carry out only an overview of the criminal-law measures of several EU countries. Important in this issue is a comparison of the research with Ukrainian realities. In particular, the practice and scientific views in the complex show that the current system of penalties under the Criminal Code of Ukraine contains its shortcomings, which, in particular, are not only systemic in nature. A separate improvement and modernization requires certain types of punishments that are part of the system. In particular, some measures of criminal-law influence not only require changes in their formulation in the criminal law in accordance with European standards, but also the exclusion in general from the Criminal Code of Ukraine because of the failure to achieve the very purpose of punishment and non-compliance with the requirements of modern Ukrainian society. In general, according to the results of the study, the authors were asked to simplify the penal system of Ukraine in accordance with the example of France, Italy, the Kingdom of the Netherlands, to change the wording in the law of the existing measures of criminal law influence in accordance with the requirements of international and European law.